In vitro regeneration of three varieties of Brassica campestris L. grown in Bangladesh - Goswami, B; Hoque, MI; Khan, S; Sarker, RH (Bangladesh Journal of Scientific and Industrial Research, 2020)
A reproducible in vitro regeneration system was developed for three varieties of Brassica campestris L. namely Agrani, BINA Sarisha-10 and BINA Sarisha-6 using hypocotyl and cotyledonary leaf with petiole as explants. MS medium supplemented with 2.0 mg/l BAP and 0.2 mg/l IAA was found to be the best for the multiple shoot formation for all the three varieties. Among three varieties, BINA Sarisha-6 showed best response in terms of shoot regeneration as well as number of shoots per explant (9.0) using hypocotyls as explants. In case of Agrani and BINA Sarisha-10 highest number of shoot per explants were found 8.2 and 7.0, respectively. Interestingly in vitro regenerated shoots of BINA Sarisha-6 and BINA Sarisha-10 were produced in vitro flowers on shoot regeneration media. Best root induction in BINA Sarisha-6, Agrani and BINA Sarisha-10 was achieved on MS media supplemented with 0.5 mg/l IBA. After proper hardening, the in vitro regenerated plantlets were successfully transplanted into soil. Bangladesh J. Sci. Ind. Res.55(3), 181-188, 2020